The relationship between school bullying victimization and social mindfulness in middle school students: a chain mediating model of self-concept clarity and cognition reappraisal - Yang, Weijing; Hu, Dong; Guo, Ying (Frontiers in Psychology, 2024)
Objective: To determine the relationship between school bullying victimization and social mindfulness and its mechanism in light of the interdependence and schema theories. Method: The Chinese version of the Delaware Bullying Victimization Scale-student, Emotion Regulation Questionnaire, Self-Concept Clarity Scale and The Social Mindfulness Self-report Scale (SMSRS) were distributed to 553 middle school students. Results: (1) The correlations of school bullying victimization with social mindfulness, self-concept clarity, and cognition reappraisal were statistically significant. (2) School bullying victimization had a significant effect on social mindfulness. (3) The simple mediating role of self-concept clarity and cognition reappraisal between school bullying victimization and social mindfulness were significant. (4) Self-concept clarity and cognition reappraisal played a chain mediating role between school bullying victimization and social mindfulness.